1995
DOI: 10.1074/jbc.270.51.30274
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-rich Region of Raf-1 Interacts with Activator Domain of Post-translationally Modified Ha-Ras

Abstract: The interaction between "switch I/effector domain" of Ha-Ras and the Ras-binding domain (RBD, amino acid 51-131) of Raf-1 is essential for signal transduction. However, the importance of the "activator domain" (approximately corresponding to amino acids 26 -28 and 40 -49) of Ha-Ras and of the "cysteine-rich region" (CRR, amino acids 152-184) of Raf-1 have also been proposed. Here, we found that Raf-1 CRR interacts directly with Ha-Ras independently of RBD and that participation of CRR is necessary for efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
161
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(178 citation statements)
references
References 30 publications
16
161
0
1
Order By: Relevance
“…Interaction with Ras at the plasma membrane probably has multiple e ects on Raf-1. First of all, Ras association is believed to drive the conformational change necessary to reverse the inhibitory e ects of the amino terminus of Raf-1 (Hu et al, 1995;Luo et al, 1997). Second, docking with Ras brings Raf-1 to the plasma membrane which is the primary site of action for vSrc, the EGF receptor and phorbol esters (Traverse et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction with Ras at the plasma membrane probably has multiple e ects on Raf-1. First of all, Ras association is believed to drive the conformational change necessary to reverse the inhibitory e ects of the amino terminus of Raf-1 (Hu et al, 1995;Luo et al, 1997). Second, docking with Ras brings Raf-1 to the plasma membrane which is the primary site of action for vSrc, the EGF receptor and phorbol esters (Traverse et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that activation of Raf by Ras requires multiple contacts with both the RBD and the zincbinding region (Brtva et al, 1995;Chuang et al, 1994). While the RBD provides a high a nity site for Ras-GTP, the zinc binding region interacts with Rasfarnesyl and is critical for the activation of the protein kinase (Chuang et al, 1994;Hu et al, 1995;Luo et al, 1997). Association with Ras dislodges 14.3.3 from CR2, possibly opening up the molecule for activation by further modi®cation (Clark et al, 1997;Rommel et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…But, surprisingly, this interaction does not augment Raf-1's catalytic activity, unless Ras is properly localized at the cell membrane [19]. Ras can interact with two domains in the Raf-1 N-terminus : the Ras-binding domain (RBD ; amino acids and the cysteine-rich domain (CRD ; amino acids [20,21]. The RBD alone is sufficient for the translocation of Raf-1 from the cytosol to the cell membrane, while the CRD is dispensable.…”
Section: A Complicated Relationship : How Ras Proteins Regulate Raf Kmentioning
confidence: 99%
“…As Ras can spontaneously form dimers in a lipid bilayer [31], and since dimerization can activate Raf-1 [32,33], such a state could comprise Ras inducing Raf-1 dimerization. An alternative, but not mutually exclusive, possibility is that Ras dimerization is needed for simultaneous binding to the RBD and CRD, which have both been shown to be contacted by the Ras effector domain [21]. A Ras dimer would elegantly resolve the steric dilemma of how the tiny Ras effector domain can engage two different domains in Raf at the same time.…”
Section: A Complicated Relationship : How Ras Proteins Regulate Raf Kmentioning
confidence: 99%
“…Recent studies show that farnesyl modification of Ha-Ras is important for high affinity interaction with (18,19) and full kinase activity of Raf-1 (20 -22). Farnesylation is also reported to increase in vitro binding of Ha-Ras and KRas4B to p110␥, a PI3-kinase catalytic subunit family member (23).…”
mentioning
confidence: 99%